Maksar hepatoprotector is an effective corrector of prednisolone immunosuppressive action at experimental toxic hepatitis - A. I. Vengerovsky; L. M. Ogorodova; T. V. Perevozchikova (Бюллетень сибирской медицины, 2003)
Polyphenol containing hepatoprotectors — maksar (complex of isoflavones and stilbenes of Far East plant — Maaсkia amurensis Rupr.et Maxim.) and legalon — during combined introduction with prednisolone to rats with chronic hepatitis, caused by tetrachloromethane, weaken the immunosuppressive action of glucocorticoid – augment the blood lymphocyte quantity, prevent the thymus atrophy, increase the blasts and antibody-forming cells content in spleen and the functional activity of with C3b-receptors in peritoneal exudation.